Total Anthocyanin Content in Intact Acai (Euterpe oleracea Mart.) and Jucara (Euterpe edulis Mart.) Fruit Predicted by Near Infrared Spectroscopy - A. Teixeira, Gustavo H. de [UNESP]; Lopes, Valquiria G.; Cunha Junior, Luis C.; Pessoa, Jose D. C. (Amer Soc Horticultural Science, 2015)
Acai (Euterpe oleraceae Mart.) and jucara (Euterpe edulis Mart.) palms are native to Brazil and these species are rich in anthocynanins. The methods applied to determine anthocyanins are time-consuming, generate chemical residues, and do not fit in modern on-line grading machines. As near infrared (NIR) spectroscopy has been used as a nondestructive method to determine anthocyanin, the objective of this study was to use NIR spectroscopy to predict total anthocyanin (TA) in intact acai and jucara fruits. Spectra were collected using a Fourier transform (FT)-NIR spectrophotometer in the diffuse reflectance (4,000-10,000 cm(-1)) and TA reference data were obtained using the Association of Official Analytical Chemists (AOAC) method. Different treatments were applied to spectra and spectral data sets were correlated with TA by using partial least squares (PLSs) regression algorithm. The global-PLS model obtained with acai and jucara spectra resulted in a root mean standard error of prediction (RMSEP) of 10.05 g-kg(-1). However, this model was not adequate for TA levels found in acai fruits, therefore individual models were developed. The acai-PLS model proved to be more adequate, as RMSEP was reduced to 3.56 g.kg(-1). On the other hand, the RMSEP obtained with the jucara-PLS model (6.59 g.kg(-1)) was almost the same of the global model. NIR spectroscopy can be used to adequately predict TA content in intact acai and jucara fruits and this method could be used as an analytical procedure to monitor their quality.
Keywords: nondestructive methods; noninvasive methods; chemometrics; PLS; postharvest; quality